NOCS Surface Flux Dataset v2.0 ... - National Oceanography Centre/University Of Southampton (UCAR/NCAR - Research Data Archive, 2008)
The National Oceanography Centre Southampton (NOCS) Version 2.0 Surface Flux Dataset is a monthly mean gridded dataset of marine surface measurements and derived fluxes constructed using optimal interpolation. Input for the period 1973 to 2006 are ICOADS Release 2.4 ship data, the update from 2007 to 2014 uses ICOADS Release 2.5 and data after 2007 are preliminary. The dataset is presented as a time series of monthly mean values on a 1 degree area grid. The quality of the gridded data is quantified by estimates of random, bias and total uncertainty. The monthly means were derived from daily estimates of each variable and the standard deviation of these daily values is also available. Click HERE [http://rda.ucar.edu/datasets/ds260.3/docs/nocs2_variable_defs.doc] for detailed variable information. Users are advised to take account of the uncertainty estimates provided, and to note that in very poorly sampled regions, such as the Southern Ocean, the uncertainty estimates themselves may be unreliable. Surface ...